Modelos de crecimiento urbano de Bogotá 2000 - 2020 : análisis morfológico de las Unidades de Planeación Zonal "Las Nieves" y "Casablanca" - Urazán González, Jessica Lorena (2023)
The compact and dispersed urban growth models of Bogotá have redefined its city outlines in the last 20 years, giving way to a production of urban space based on closed forms that have not been able to articulate with each other. The following research study has pointed out the importance of advancing in the comprehensive understanding of the production of urban space, through the analysis of the physical form, perceived and represented, being an integral part to deepen the study of urban transformations. The study of morphology is essential to understand the physical space-temporal structures left by the growth of the city, but it is also an integral part of understanding the relationship of the inhabitants with the form. Since ultimately society is the one that receives information about changes in urban space, and at the same time participates in shaping it through its experiences and meanings.